Islam and extremism - Ushama, Thameem (ISTAC-IIUM Publications, 2021)
Contents Transliteration Table ix Foreword xi Preface xv Introduction: Definition of Arabic Terms 1 PART I 1. Western Scholars’ Perspective of Muslim Extremism 11 PART II 2. Islam: A Religion of Moderation or Extremism? 49 3. Islam: A Religion of Tolerance or Intolerance? 79 4. Islam: A Religion of Ease or Hardship? 115 5. Islam: A Religion of Peace or Force? 151 PART III 6. The Roots, Causes and Nature of Extremism 187 7. Extremism in Muslim Life and the Concept of Jamāᶜah 217 8. Muslims’ Recourse to Takfīr 253 9. Historical Roots of Radical Islamist Thinking 289 PART IV 10. The Phenomenon of Terrorism 323 Bibliography 359 Index 367